The Effect of Serotonin-Targeting Antidepressants on Neurogenesis and Neuronal Maturation of the Hippocampus Mediated via 5-HT1A and 5-HT4 Receptors - Segi-Nishida, Eri (Frontiers in Cellular Neuroscience, 2017)
Antidepressant drugs such as selective serotonin reuptake inhibitors (SSRIs) specifically increase serotonin (5-HT) levels in the synaptic cleft and are widely used to treat mood and anxiety disorders. There are 14 established subtypes of 5-HT receptors in rodents, each of which has regionally different expression patterns. Many preclinical studies have suggested that the hippocampus, which contains abundant 5-HT1A and 5-HT4 receptor subtypes in the dentate gyrus (DG), is critically involved in the mechanisms of action of antidepressants. This review will analyze studies demonstrating regulation of hippocampal functions and hippocampus-dependent behaviors by SSRIs and similar serotonergic agents. Multiple studies indicate that 5-HT1A and 5-HT4 receptor signaling in the DG contributes to SSRI-mediated promotion of neurogenesis and increased neurotrophic factors expression. Chronic SSRI treatment causes functions and phenotypes of mature granule cells to revert to immature-like phenotypes defined as a ‘dematured’ state in the DG, and to increase monoamine reactivity at the dentate-to-CA3 synapses, via 5-HT4 receptor signaling. Behavioral studies demonstrate that the 5-HT1A receptors on mature GCs are critical for expression of antidepressant effects in the forced swim test and in novelty suppressed feeding; such studies also note that 5-HT4 receptors mediate neurogenesis-dependent antidepressant activity in, for example, novelty-suppressed feeding. Despite their limitations, the collective results of these studies describe a potential new mechanism of action, in which 5-HT1A and 5-HT4 receptor signaling, either independently or cooperatively, modulates the function of the hippocampal DG at multiple levels, any of which could play a critical role in the antidepressant actions of serotonin-enhancing drugs.